Axiological concept of LAZINESS as an object of linguistics and psychology - Wang , Lili (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2024)
Modern linguistics is a polyparadigmatic science, which is distinguished, in particular, by its interest in the data of psychology. It is especially important to involve the results of psychology during the study of axiological concepts, since it must be taken into account that the assessments made by people do not always have sufficient grounds. The purpose of the research is to consider the concept of LAZINESS from the point of view of various sciences, in particular cognitive linguistics and psychology, supplementing the linguistic data with knowledge about the causes of the studied condition.Applying a cognitive approach to the study of linguistic phenomena, we focused on differentiating the contextual meanings of the polysemic word лень: according to the criterion “character of conceptualization”, we distinguish perceptual meanings, meanings of the internal state of the subject-experiencer, and inferential meanings.The methods of cognitive semantics made it possible to generalize the set of contextual meanings of the word; to reveal the repetitive structure of cognitive processes, in which patterns of understanding and thinking are reflected, to reconstruct such a Gestalt scenario: in the center of the simulated situation is a person who is negatively evaluated from the point of view of attitude towards laziness; assessment arises as a result of the discrepancy between the physical / psychological / psychophysiological state, character, behavior of a lazy person and the expected socio-cultural norm. Evaluation is carried out by the speaker / narrator. Since the concept of LAZINESS is inseparable from its antipode WORK, the socio-cultural norm is associated with opposite meanings: “a person should work hard, be hardworking, etc.”From the point of view of psychology, the characteristic of a lazy person is often biased and is not always based on the study of the motives of the person being evaluated. The concept of laziness can be a reductionist explanation for why others do not act as expected. At the same time, the real motivation, abilities and qualifications of the evaluated person are almost never taken into account. These problems are explained in the discourse of psychology. Analysis of psychological literature made it possible to identify the main causes of laziness: low level of motivation; weak willpower; desire for satisfaction; a protective reaction against physical or mental stress; a kind of protest against violence against a person and some others.